Intra- and interspecific variability among congeneric Pagellus otoliths - Claudio D’Iglio (Nature Portfolio, 2021)
Abstract Otolith features are useful tools for studying taxonomy, ecology, paleontology, and fish biology since they represent a permanent record of life history. Nevertheless, the functional morphology of otoliths remains an open research question that is useful to completely understand their eco-morphology. This study aims to deepen the knowledge of intra- and interspecific variation in sagitta morphology in three congeneric seabreams, to understand how such variability could be related to the lifestyles of each species. Therefore, the sagittae (n = 161) of 24 Pagellus bogaraveo, 24 Pagellus acarne, and 37 Pagellus erythrinus specimens, collected from the south Tyrrhenian Sea, were analyzed using scanning electron microscopy and a stereomicroscope to assess morphometric features, variability between otolith pairs and the external crystalline structure the of sulcus acusticus. Statistical analysis demonstrated that, between the species, variability in sagittal otolith rostral length growth and sulcus acusticus features, correlated with increased fish total length and body weight. Moreover, slight differences between otolith pairs were detected in P. acarne and P. erythrinus (P < 0.05). The results confirm changes in otolith morphometry and morphology between different congeneric species and populations of the same species from different habitats.